2012
DOI: 10.1515/sg-2012-0007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monoclonal and assorted seedling rootstocks on long term growth and yield of Hevea clones

Abstract: Seven Hevea brasiliensis clones were evaluated on two types of rootstocks, assorted seedling rootstocks (AR) and monoclonal rootstock (MR) over 19 years. Influence of rootstock on scion growth and rubber yield was assessed based on juvenile height, circumference of the main trunk (cm), number of branches, branching height and cumulative dry rubber yield (g per tree per tapping, conventionally abbreviated gt-1t-1). Highest cumulative yield (g per tree per tapping) over the 12 years for which the trees were tapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Several studies showed that the combination of rootstocks and scion determined the incompatibility, growth, and yield [13,14]. A study by [15] suggested that the rootstock and scion interaction did not influence rubber yield significantly, implied that the assorted seeds were acceptable for rootstock seedlings. The root accumulation rate (RAR) and shoot accumulation rate (SAR) of the samples indicated that the biomass accumulation rate was not significantly different among treatments (Table 2).…”
Section: Biomass Accumulationmentioning
confidence: 99%
“…Several studies showed that the combination of rootstocks and scion determined the incompatibility, growth, and yield [13,14]. A study by [15] suggested that the rootstock and scion interaction did not influence rubber yield significantly, implied that the assorted seeds were acceptable for rootstock seedlings. The root accumulation rate (RAR) and shoot accumulation rate (SAR) of the samples indicated that the biomass accumulation rate was not significantly different among treatments (Table 2).…”
Section: Biomass Accumulationmentioning
confidence: 99%
“…Nesse sentido, ao avaliarem sete clones de seringueira sobre porta-enxertos de mudas sortidas e portaenxertos de mudas monoclonais, Gireesh et al (2012) não observaram evidência para sugerir que o crescimento e rendimento de clones foi significativamente influenciado pelo tipo de porta-enxerto, aos 12 anos após o início da extração do látex. Contudo, Arantes et al (2010) afirmam que sementes de origem desconhecida, que possam ter sido coletadas em jardins monoclonais, podem originar p lantas com baixo vigor.…”
Section: Introductionunclassified